The Indonesian Version of Evidence-Based Practice Questionnaire (EBPQ): An Evaluation of Reliability - Melati Fajarini; Sri Rahayu; Agus Setiawan (Indonesian Contemporary Nursing Journal, 2021)
Introduction: The use of evidence-based practice (EBP) has been demonstrated to increase the quality of patient care. However, the extent to which it is practiced in Indonesia is yet to be determined. It was necessary to develop a means of measuring EBP in order to acquire a profile of the use of EBP in Indonesia. The EBP questionnaire (EBPQ) developed by Upton and Upton was selected in the current study to evaluate the perceptions of healthcare workers regarding their knowledge of, attitudes toward, and practice of EBP. This questionnaire is widely recognized; however, an Indonesian version has not yet been developed. This study aimed to translate the EBPQ developed by Upton and Upton into Indonesian and to evaluate its reliability. Method: WHO framework on how to translate and adapt an instrument was applied. On completion of the forward translation and discussion process, backward translation of the EBPQ was performed, after which it was pretested and finalized. Reliability was tested by testing the questionnaire on 42 nurses at five hospitals in Depok and Jakarta. Result: Four words were changed. All items are valid. The reliability analysis resulted Cronbach’s a of 0.96 (a = 0.92, 0.80, and 0.96 for practice, attitude, and knowledge, respectively. Thus, 24 translated statements determined to be valid and reliable, were included in the final version. Conclusion: The Indonesian translated version of the EBPQ proposed by Upton and Upton was demonstrated to be valid and reliable. Further studies on the perceptions of healthcare workers  are warranted.